X‐Ray‐Visible Microcapsules Containing Mesenchymal Stem Cells Improve Hind Limb Perfusion in a Rabbit Model of Peripheral Arterial Disease12. (15th May 2012) - Kedziorek, Dorota A.; Hofmann, Lawrence V.; Fu, Yingli; Gilson, Wesley D.; Cosby, Kenyatta M.; Kohl, Bernard; Barnett, Brad P.; Simons, Brian W.; Walczak, Piotr; Bulte, Jeff W.M.; Gabrielson, Kathleen; Kraitchman, Dara L.
Abstract: The therapeutic goal in peripheral arterial disease (PAD) patients is to restore blood flow to ischemic tissue. Stem cell transplantation offers a new avenue to enhance arteriogenesis and angiogenesis. Two major problems with cell therapies are poor cell survival and the lack of visualization of cell delivery and distribution. To address these therapeutic barriers, allogeneic bone marrow‐derived mesenchymal stem cells (MSCs) were encapsulated in alginate impregnated with a radiopaque contrast agent (MSC‐Xcaps.) In vitro MSC‐Xcap viability by a fluorometric assay was high (96.9% ± 2.7% at 30 days postencapsulation) and as few as 10 Xcaps were visible on clinical x‐ray fluoroscopic systems. Using an endovascular PAD model, rabbits ( n = 21) were randomized to receive MSC‐Xcaps ( n = 6), empty Xcaps ( n = 5), unencapsulated MSCs ( n = 5), or sham intramuscular injections ( n = 5) in the ischemic thigh 24 hours postocclusion. Immediately after MSC transplantation and 14 days later, digital radiographs acquired on a clinical angiographic system demonstrated persistent visualization of the Xcap injection sites with retained contrast‐to‐noise. Using a modified TIMI frame count, quantitative angiography demonstrated a 65% improvement in hind limb perfusion or arteriogenesis in MSC‐Xcap‐treated animals versus empty Xcaps. Post‐mortem immunohistopathology of vessel density by anti‐CD31 staining demonstrated an 87% enhancement in angiogenesis in Xcap‐MSC‐treated animals versus empty Xcaps. MSC‐Xcaps represent the first x‐ray‐visible cellular therapeutic with enhanced efficacy for PAD treatment. STEM CELLS 2012;30:1286–1296